Hemothorax Complicating Bronchial Artery Aneurysm - Riyad Karmy-Jones; Dawn Hastreiter; Thomas Burdick (Canadian Respiratory Journal)
An elderly patient presented with spontaneous hemothorax. Workup identified a right-sided bronchial aneurysm as the source, which was successfully embolized. Bronchial aneurysms can be managed by interventional techniques, although the choice of approach depends upon the clinical and anatomical settings.